Use of Graphics Processors in Data Compression Algorithms - Uchkunovna, Khalilova Shahnoza (Universitas Muhammadiyah Sidoarjo, 2022)
Query co-processing on graphics processors (GPUs) has become an effective means to improve the performance of main memory databases. However, this co-processing requires the data transfer between the main memory and the GPU memory via a lowbandwidth PCI-E bus. The overhead of such data transfer becomes an important factor, even a bottleneck, for query co-processing performance on the GPU. In this paper, we propose to use compression to alleviate this performance problem.